Research and prospect on economic value evaluation and pricing mechanism of spectrum resources - Jie DONG; Hengzhi LI; Yan CHEN; Wenjuan WANG (Dianxin kexue)
Firstly, from the perspective of natural resource value, the value composition, timeliness, integrity, structure and sociality of value characteristics and value existence forms of spectrum resources were explained, and the definition and connotation of economic value evaluation and pricing of spectrum resources were given.Finally, the pricing methods of spectrum resources, such as the pricing method based on spectrum fee, the pricing method based on administrative fee, the pricing method based on user’s gross income and the opportunity cost method, and the pricing methods of spectrum resources adopted by some countries were sorted out and analyzed, and some suggestions were put forward to further improve the economic value evaluation and pricing mechanism of spectrum resources in China.